Implementation of Health Protocol Policy in Managing the Covid-19 Pandemic in State 13 Vocational School (SMK) City of Bekasi - Pangestu, Fazri Sukmatira; Ahmed, Abdussalam Ali (Yayasan Sinergi Kawula Muda, 2023)
The purpose of this study was to determine the implementation of health protocol policies at SMK Negeri 13 Bekasi City. The research method used is descriptive qualitative, namely describing problems related to events that arise around the researcher, and the type of research used is phenomenology, namely examining an event or events that occur in the present. The data sources used are primary data sources and secondary data with 8 informants. Data collection techniques using interviews, observation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of the research conducted showed several indicators in the form of Implementation, Theory. Hanifah Harsono regarding the implementation of communication, resources, disposition, and organizational structure of the obstacle factors, the inhibiting factors, namely, the Quality and Quantity of Human Resources, Facilities and Infrastructure, Budget. Efforts or solutions regarding the implementation of health protocol policies, namely, Improving the quality and quantity of human resources (HR) of SMK Negeri 13 Bekasi City, Adding and improving infrastructure, Increasing and making the best possible use of the budget, Increasing school community awareness of the dangers of the COVID-19 disease outbreak ,.Human behavior that still lacks awareness of the Health Protocol.